Investigating E-Government Adoption: The Intention to Use MyASN Application by Indonesian National Civil Service Agency (NCSA) - Silfa Kurnia Aditya; Husna Alfiani; Dana Indra Sensuse; Sofian Lusa; Prasetyo Adi Wibowo Putro; Sofianti Indriasari (Journal of Government and Civil Society, 2024)
This study investigates the implementation of e-government initiatives in Indonesia, specifically focusing on the MyASN application designed for civil servants. Despite the introduction of MyASN, challenges persist in terms of user acceptance, and its complete utilization among civil servants throughout Indonesia is yet to be achieved. The primary goal of this research is to comprehensively identify the factors influencing the adoption of MyASN among civil servants using Unified Theory of Acceptance and Use of The Technology (UTAUT) conceptual model. The target population is respondents who use the MyASN application. The target population is respondents who use the MyASN application. This research obtained a total of 182 respondents who filled out the questionnaire via Google Forms, which were then analyzed using the Structural Equation Model (SEM) approach with SmartPLS software. The findings highlight that behavioral intention, performance expectation, and social influence are factors influencing users' intention to use the My-ASN application. On the other hand, effort expectancy and facilitating condition donâ€™t affect users' intention and behavior in adopting MyASN. Furthermore, concerning moderating variables, only working experience and voluntariness of use influence user behavior, although their impacts are not very significant.Â Penelitian ini mengkaji terkait implementasi e-government di Indonesia, khususnya berfokus pada aplikasi MyASN yang dirancang untuk Aparatur Sipil Negara (ASN). Meskipun aplikasi MyASN ini telah disosialisasikan, namun pada implementasinya masih terdapat tantangan dalam penerimaan penggunanya dan pemanfaatannya yang belum maksimal di kalangan ASN di seluruh Indonesia. Tujuan utama dari penelitian ini adalah mengidentifikasi faktor apa saja yang mempengaruhi niat pengguna untuk menggunakan aplikasi MyASN menggunakan metode UTAUT (Unified Theory of Acceptance and Use of The Technology). Target populasi adalah responden yang menggunakan aplikasi MyASN. Penelitian ini memperoleh sebanyak 182 responden yang mengisi kuisioner melalui Google Forms, kemudian dilakukan analisis menggunakan pendekatan SEM (Structural Equation Model) dengan perangkat lunak SmartPLS. Temuan penelitian ini menjelaskan bahwa behavioral intention, performance expectation, dan social influence merupakan faktor yang mempengaruhi niat pengguna dalam menggunakan aplikasi My-ASN. Disisi lain, effort expectancy dan facilitating condition tidak mempengaruhi niat dan perilaku pengguna dalam mengadopsi MyASN. Selain itu, pada moderating varible, hanya working experience dan voluntariness of use yang mempengaruhi perilaku pengguna, meskipun dampaknya tidak terlalu signifikan.